Keadilan Restoratif dalam Penyelesaian Tindak Pidana Pemalsuan Surat pada Perjanjian Kredit: Studi Kasus BPR NBP 24 Duri - Riko Slamat Tampati; Sriono Sriono; Wahyu Simon Tampubolon; Indra Kumala Sari (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study analyzes the shift from punitive to restorative paradigms in resolving document forgery within banking credit agreements. Using an empirical legal approach, the research evaluates how restorative justice mechanisms effectively address fraud involving dual collateral documents at BPR NBP 24 Duri. The findings reveal that document forgery in this context is not merely a breach of contract but a systemic failure in collateral verification that necessitates legal restoration. The study’s novelty lies in its analysis of the "economic recovery" function of Police Regulation No. 8 of 2021, which transforms criminal threats into a tool for debt restitution. It concludes that restorative justice offers a pragmatic solution for financial crimes by prioritizing asset recovery over imprisonment. This research contributes to the development of Indonesian criminal law by providing a framework for resolving hybrid private-criminal disputes through non-litigation channels.